DETERMINANTS OF OUTPUT OF CASSAVA (MANIHOT SPECIES) PRODUCTION IN ABUJA, NIGERIA (American International Journal of Agricultural Studies, 2022)
This research study focused on determinants of the output of cassava (Manihot species) production in Abuja, Nigeria. Multi-stage method of sampling was used. One hundred (100) cassava farmers were sampled and selected. Primary data were obtained through the use of a well-designed and also well-structured questionnaire. Data were analyzed using econometrics and statistical tools. The results show that 87% of cassava producers were between 31 to 50 years of age. About 72% had formal education and were literate. Averagely, they had 4.76 hectares of cassava farmland. The estimated gross margin (GM) and net farm income (NFI) of cassava production per hectare were 1,464, 162.72 Naira and 1, 453, 752.49 Naira respectively. This implies that cassava production was profitable and worthwhile. Farm size and fertilizer input were statistically significant factors influencing the output of cassava production. Age, labour input, and cassava cuttings were statistically significant factors influencing the output of cassava production. While chemical input statistically and significantly influenced the output of cassava production. The constraints facing cassava producers were the unavailability of improved cassava cuttings, the high cost of farm inputs, insecurity, inadequate extension services, and inadequate finances. The research study recommends that improved cassava cuttings should be made available to farmers for increased productivity. Extension officers should be employed to disseminate innovations, research findings, and new farm technologies to cassava farmers. Credit or loan facilities should be made available to cassava producers at low-interest rates.JEL Classification Codes: Q1, Q3, Q5.